Monitoramento da atenuação natural de álcool etílico hidratado combustível em escala laboratorial por meio de métodos geofísicos - Braga, Antonio Celso de Oliveira [UNESP]; Moreira, César Augusto [UNESP] (Lepidus Tecnologia, 2012)
Currently has few studies today concerning the behavior of the ethyl alcohol hydrated combustible in the geological environment, results of eventual spill or leaks in a wide transport chain and distribution. This work discusses the results of an experiment in laboratorial scale, that involves the monitoring of alterations in physical properties a simulate leak of alcohol in a tank with sand saturated in water, during 4920 hours. Are applied electrical resistivity, induced polarization and spontaneous potential geophysical methods. The electric resistivity is clearly correlating to the ethanol degradation pattern. The chargeability demonstrated sensibility to this pattern, while the natural electric potential revealed direct association with the oscillations of groundwater level. The variability of the physical parameters monitoring probable control for ethanol degradation process in environment study.

Atualmente existem poucos estudos acerca do comportamento do álcool etílico hidratado combustível no ambiente geológico, fruto de eventuais derrames ou vazamentos numa ampla cadeia de transporte e distribuição. Este trabalho discute os resultados de um experimento em escala laboratorial, que envolve o monitoramento de alterações em propriedades físicas de um vazamento simulado de álcool, num tanque com areia parcialmente saturada em água, durante 4920 horas. Foram utilizados os métodos geofísicos de eletrorresistividade, polarização induzida e potencial espontâneo. A resistividade elétrica foi claramente correlacionável ao padrão de degradação do etanol. A cargabilidade demonstrou sensibilidade a este padrão, enquanto que o potencial elétrico natural revelou associação direta com as oscilações do nível freático. A variabilidade dos parâmetros físicos monitorados foi possivelmente controlada por processos de degradação do etanol no ambiente estudado.
Natural attenuation monitoring of the ethyl alcohol hydrated combustible in laboratorial scale for geophysical methods
Keywords: Electrical profiling; Aerobic; Oxidation; Applied geophysics; Perfilagem elétrica; Aeróbico; Oxidação; Geofísica aplicada